(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
Background: Clopidogrel (CLOP) has been used as an antiplatelet medication for many years to treat strokes; however, CLOP resistance may increase the risk of stroke recurrence. The poor metabolism of CLOP, which leads to resistance, is thought to be caused by the CYP2C19 (C-19) loss of function (LoF) polymorphism. It was impossible to draw firm conclusions from earlier research since the data were so inconsistent and diverse. Aim: The current study was conducted to gather conclusive data from an updated meta-analysis about the relationship between C-19LoF(C-19-LoF) polymorphism and coronary artery (CA) events in individuals using CLOP. Methodology: Electronic databases PubMed, EMBASE, SciHub, and Google Scholar were used to extract data till November 2024. RevMan 5 software was used for the analysis of extracted data. Results: Out of 7582 articles, we used 90 carefully selected to conduct our meta-analysis, which comprised 52,748 patients with CA disease undergoing CLOP medication. Conclusion: Our results indicate that CA events and composite events are significantly more common in individuals with one or more C-19-LoF alleles worldwide than in those without these alleles, particularly in Asian populations. The C-19-LoF alleles put the entire population at risk for composite events and recurrent CA events, especially Asians on CLOP, according to our meta-analysis. For people with poor or intermediate metabolic activity, more study is needed on alternate antiplatelet treatments.